Effect of an Open Water Body on Tsunami Inundation and Forces Exerted on a Structure - Arefiseresht, Reza (Université d'Ottawa / University of Ottawa, 2026)
Tsunamis are highly destructive natural hazards that pose severe risks to coastal communities and infrastructure. Their unpredictable occurrence, long wavelengths, and large flow depths often generate extreme loads that can exceed the resistance of coastal and onshore structures. Recent tsunami events have demonstrated that even engineered buildings and protective systems may suffer significant damage or failure, underscoring the need for effective mitigation strategies capable of reducing flow energy and structural loading before impact. Consequently, both engineered and nature-based countermeasures have been explored to attenuate tsunami energy, protect built infrastructure, and reduce loss of life. Among engineered mitigation measures, water-filled canals located upstream of coastal infrastructure have been identified as a potentially effective yet relatively under-investigated solution. Field observations and recent studies suggest that such canals can modify bore propagation by inducing flow deceleration and redistributing momentum prior to interaction with downstream structures. However, the hydrodynamic interaction between tsunami bores, water-filled canals, and structural elements remains complex and insufficiently understood. This study investigates the effectiveness of rectangular water-filled canals as a tsunami mitigation countermeasure through a combination of laboratory-scale experiments and calibrated numerical simulations. A series of physical experiments was conducted at a 1:10 geometric scale to reproduce tsunami-like bores using a rapid-release gate mechanism, analogous to a dam-break flow. This approach enabled controlled and repeatable generation of bores with well-defined initial conditions. Bore depth time histories were measured at several locations along the flume to capture the evolution of the flow before, and after the canal. A rigid square column was installed downstream of the canal, and a loadcell was used to record horizontal force time histories during bore impact. The canal geometry was systematically varied to evaluate its influence on bore transformation and structural loading. The experimental results indicate that the presence of a water-filled canal significantly alters bore characteristics, most notably by reducing the bore front velocity prior to impact. Under the tested conditions, the canal reduced the peak horizontal force acting on the downstream column compared to the no-canal configuration. To extend the investigation beyond laboratory-scale constraints and to examine a wider range of canal geometries, numerical simulations were performed using the FLOW-3D computational fluid dynamics model. The numerical model was calibrated against the experimental measurements to ensure accurate reproduction of free-surface evolution, bore propagation, and force response. Following validation, the model was applied at prototype scale to simulate a tsunami-like bore generated by a 4 m-deep dam-break flow interacting with water-filled canals of varying widths and depths. The numerical results corroborate the experimental findings and provide further insight into the role of canal geometry in force mitigation. The simulations demonstrate that horizontal force reduction is strongly dependent on canal dimensions, with canal width exerting a substantially greater influence than canal depth. Maximum force reductions of approximately 40% were achieved for a canal 40 m wide and 4.5 m deep. The results also reveal the existence of performance thresholds for both geometric parameters, beyond which further increases in width or depth result in diminishing returns in terms of force reduction. Analysis of flow fields from the numerical simulations indicates that the canal promotes flow expansion, momentum redistribution, and partial energy dissipation, leading to reduced momentum flux at the downstream structure. Overall, the combined experimental and numerical results demonstrate that rectangular water-filled canals can meaningfully attenuate tsunami bore energy and significantly reduce hydrodynamic forces acting on downstream coastal structures. The findings emphasize the dominant role of canal width in force mitigation and identify practical geometric limits relevant for design. This study provides new insight into bore-canal and bore-structure interactions and supports the consideration of water-filled canals as an effective engineered countermeasure for reducing structural damage in tsunami-prone coastal regions.
Keywords: Tsunami bore; Mitigation countermeasure; Experimental test; Numerical modeling; Water-filled canal